Pengembangan Media Pembalajaran Interaktif Sebagai Media Pembelajaran Bahasa Arab di Ponpes An Nur Pungging Mojokerto - Fitriyah, Khoirunnisail; Jannah, Agustin Nur (Al-Qalam Institute, 2023)
The purpose of this community service activity is to add experience about the latest learning media so that it is applied to learning in Islamic boarding schools, so that learning becomes interesting and easy for students to understand. The methods used in this community service activity are Observation, Forum Group Discussion, Direct interviews, Outreach, mentoring and Evaluation of Results and Simulations on the use of Arabic Interactive Media. Evaluation of the success of this service program is carried out by distributing questionnaires after the activity is carried out. The result of this community service activity is a positive response given by the asatidz board to this interactive media development activity because they gain new knowledge and experience so that further learning is more creative and innovative.